Hyperglycemia Interacts with Ischemia in a Synergistic Way on Wound Repair and Myofibroblast Differentiation. Issue 7 (July 2015) - Tobalem, Mickaël; Lévigne, Dominik; Modarressi, Ali; Atashi, Fatemeh; Villard, Frederic; Hinz, Boris; Pittet-Cuénod, Brigitte
Abstract : Background: Hyperglycemia is known to adversely affect the outcome of ischemic insults, but its interaction with ischemia has not been investigated in wound repair yet. In this study, we develop a new animal model allowing to investigate the interaction between hyperglycemia and ischemia during the wound repair process. We focus on myofibroblast differentiation, a key element of wound repair. Methods: Ischemia was inflicted in Wistar rats by resection of the femoral to popliteal arteries on the left side, whereas arteries were dissected without resection on the right side. Full-thickness skin wounds (1 cm 2 ) were created on both feet. Hyperglycemia was induced by injection of streptozotocin. Normoglycemic animals served as control ( n = 23/group). Blood flow, wound closure, and myofibroblast expression were measured. Results: Wound closure was significantly delayed in ischemic compared with nonischemic wounds in all rats. This delay was almost 5-fold exacerbated in hyperglycemic rats compared with normoglycemic rats, while hyperglycemia alone showed only a slight effect on wound repair. Delayed wound repair was associated with impaired wound contraction and myofibroblast differentiation. Conclusions: Our model allows to specifically quantify the effect of hyperglycemia and ischemia alone or in combination on wound repair. We show that hyperglycemia amplifies the inhibitory effect of ischemia on wound repair and myofibroblast expression. Our data reveal for the first time the synergic aspect of this interaction and therefore stress the importance of a strict glycemic control in the management of ischemic wounds.